Enter XML: the future markup language / Hamdan Abdul Maad - Abdul Maad, Hamdan (2000)
XML and HTML are both subsets of SGML. XML is a markup language for describing structured data where the content is separated from presentation. To process an XML document, a software program is needed: XML parser (an XML processor) - currently IE5 support XML and Nestcape through Morzilla.org. XML provides a file format for representing data and a schema for data to include a description of its own structure. XML is a standard, extensible, universal format for Web-based data. With its powerful expressiveness and flexibility, XML promises to add structure to data on the Internet, bringing the Web one step closer to realizing the potential for universal communication with anyone, anywhere. Using XML with XSL or CSS, Web site's content and style can be managed, and changed in one place (the style sheet) instead of editing piles of HTML files. Using SAX or DOM, the Web document can be treated as object structures and process them in general and clean way. Developers who learn XML now will find it a powerful tool for data representation, storage, modeling, and interoperation. XML will not be one of those heralded technological advances that falls after huge investments have been made. It is here, and here to stay. So, enter XML, the future markup language.